Clergy Work Orientation Profiles and Wellbeing at Work: A Study of the Lutheran Clergy in Finland - Tervo-Niemelä, Kati (Review of religious research, 2016)
This study examines work orientation and its connections to wellbeing at work among the clergy. Using k-means clustering, the article aims to build a typology of clergy members' work orientation and analyze wellbeing at work among different types of clergy members. The study is based on a survey conducted in 2014 among the clergy in the Evangelical Lutheran Church of Finland (N = 562). The results of the study show that the clergy have clear and distinctive work orientation profiles and that these profiles also have a clear linkage to wellbeing at work. Four clergy profiles were identified: clergy with a multifaceted orientation (47 %); clergy oriented towards worship life (29 %); clergy oriented towards promoting justice and helping (19 %); and clergy with a passive orientation (6 %). The study strongly suggests that clergy members with the broadest orientation and interests are most able to deal with the multifaceted demands of church work. A multiple orientation seemed to serve as a strong supporting factor at work, and by being oriented to a broad range of activities, this group also enjoyed more potential sources of support and more joyful experiences at work. Those oriented towards worship life drew their main support from the spiritual aspects of work, but they were most likely to suffer from a lack of social competence. Those oriented toward promoting justice and helping received most support from encountering people. At the same time those who were passively oriented in their work experienced the least satisfaction and the least support.